Conscientious Consumerism Project in an Undergraduate Quality Management Class. (January 2014) - Helms, Marilyn M.
ABSTRACT This article describes a "conscientious consumerism" project that involves the student as the consumer to either commend or complain to a company about a recent product or service experience. This activity and presentation helps students develop an understanding of the commendation/complaint management process within organizations while adding realism with the student as the customer. Students initiate communication with an organization and maintain a timeline of all contacts, calls, e‐mails, letters, and visits to the company as they work to resolve or report their issue. The project begins early in the semester and concludes with a final registered, certified letter to the company CEO where students summarize the class project and praise processes or recommend any needed changes. When the project is presented, students learn how organizations manage and process customer feedback and complaints. Students have insightful comparisons of the implementation and execution of such processes within organizations. The project contributes to student learning and understanding of numerous key objectives of quality management including: how quality is managed in organizations, the strategic focus customer feedback can play in organizations, process management, voice of the customer, and benchmarking best compliment/complaint management practices.